2001
DOI: 10.1006/mthe.2001.0291
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Regulated Stem Cell-Mediated Gene Therapy for Bone Regeneration

Abstract: Regulated expression of transgene production and function is of great importance for gene therapy. Such regulation can potentially be used to monitor and control complex biological processes. We report here a regulated stem cell-based system for controlling bone regeneration, utilizing genetically engineered mesenchymal stem cells (MSCs) harboring a tetracycline-regulated expression vector encoding the osteogenic growth factor human BMP-2. We show that doxycycline (a tetracycline analogue) is able to control h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
212
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(221 citation statements)
references
References 54 publications
6
212
0
3
Order By: Relevance
“…In this study, we created 6-mm-diameter defects with a total defect area more than two-fold larger than in the established 4-mm-diameter defects, because larger defects appeared more suitable for a comparison of the efficacy of two gene transfer methods. Previous gene therapy studies 22,31 showed that cellmediated BMP-2 gene transfer using the stably transfected mesenchymal progenitor cell line C3H10T1/2 resulted in enhanced bone defect repair in a mice nonunion fracture model. Our study focused on differences in the extent and pattern of new bone formation following liposome-mediated or adenoviral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we created 6-mm-diameter defects with a total defect area more than two-fold larger than in the established 4-mm-diameter defects, because larger defects appeared more suitable for a comparison of the efficacy of two gene transfer methods. Previous gene therapy studies 22,31 showed that cellmediated BMP-2 gene transfer using the stably transfected mesenchymal progenitor cell line C3H10T1/2 resulted in enhanced bone defect repair in a mice nonunion fracture model. Our study focused on differences in the extent and pattern of new bone formation following liposome-mediated or adenoviral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies which have shown evidence for skeletal regeneration in vivo using ex vivo modified stromal cells, myoblasts, or fibroblasts, 10,15,16,22,24,25 our study is unique in that it provides quantitative data on the extent of healing by valid bone density measurements. Furthermore, our data demonstrate that the healing of a critical calvarial defect is dependent on the time of exposure, as well as the number of BMP4-expressing stromal cells implanted.…”
Section: Bmp4-producing Cells Were Identified By Immunostaining (Browmentioning
confidence: 99%
“…BMP-2, approved by Food and Drug Administration (FDA) for clinical practice, is the most potent member in promoting bone and cartilage development and therefore wins a popular choice for MSCs-based BTE (Lieberman et al, 1998;Lieberman et al, 1999;Lou et al, 1999;Turgeman et al, 2001;Olmsted-Davis et al, 2002;Blum et al, 2003;Gugala et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Kumar et al, 2004;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). The BMP-2-modified MSCs are proven to increase the alkaline phosphatase (ALP) activity, mineralization, and cell proliferation in vitro and induce ectopic bone formation, heal critical size bone defect, repair fracture, and trigger spinal fusion in vivo (Lou et al, 1999;Moutsatsos et al, 2001;Turgeman et al, 2001;Blum et al, 2003;Park et al, 2003;Riew et al, 2003;Tsuda et al, 2003;Hasharoni et al, 2005;Egermann et al, 2006;Feeley et al, 2006). BMP-7 plays a key role in osteoblast differentiation, and there is only one study in which MSCs are engineered with BMP-7.…”
Section: Applicable Genes For Mscs Modificationmentioning
confidence: 99%